Effect of Epidural Air Injection on Catheter Complications. Issue 1 (January 1985) - Philip, Beverly K.
Abstract : Injection of air into the epidural space before insertion of a catheter was performed in 132 parturients. The incidence of paresthesia was thereby reduced from 49% to 29% (p < .025). The incidence of blood vessel puncture was reduced from 5.8% to 1.6% (not significant) and dural puncture did not occur. No complications were associated with this technique.